11 The impact of cardiac magnetic resonance viability assessment on the management of patients with ischaemic heart disease and left ventricular dysfunction. (26th April 2015) - Cole, BR; Douglas, H; Soong, CM; Horan, P; Dixon, LJ; Johnston, N; Harbinson, M
Abstract : Background: Identifying patients with ischaemic left ventricular dysfunction that would benefit from revascularisation is challenging. The aim of this study was to investigate the role of cardiovascular magnetic resonance (CMR) imaging in the decision making process in patients being considered for revascularisation. Methods: All patients referred for CMR viability assessment at a regional centre were identified retrospectively between January 2011 and March 2013. Patient records were reviewed to determine the revascularisation strategy and patient outcomes. Results: 324 consecutive patients were identified, of which 256 were being considered for revascularisation. The remainder were undergoing viability assessment for other reasons. Of the patients being considered for revascularisation, 38 (14%) had preserved left ventricular (LV) systolic function, 33 (17%) mild LV dysfunction, 77 (28%) moderate LV dysfunction and 108 (40%) severe LV dysfunction. Of the patients with severe LV dysfunction 22 subsequently underwent coronary artery bypass grafting (CABG), 30 had percutaneous coronary intervention (PCI) and the remaining 56 patients were managed medically. Patient characteristics and outcomes at the end of the follow-up period (median, 28 months) are detailed in Table 1 . Death from any cause occurred in 3 (14%) patients in the CABG group, 4 (13%) in the PCI group and 14 (25%) in the medical-therapy group (p = 0.32). Hospitalisation for cardiac causes occurred in 1 patient (5%) in the CABG group, 1 (3%) in the PCI group and 28 (50%) in the medical-therapy group (p < 0.001). Increased cardiac hospitalisation in the medical therapy group was primarily related to admissions with heart failure (73%). Conclusions: Patients undergoing surgical revascularisation had significantly less adverse remodelling than those managed with PCI or medical therapy. Patients undergoing CABG with viability prior to revascularisation demonstrated good outcomes, similar to those undergoing PCI. The medical therapy group had a significantly higher number of non-viable segments and outcome was poor.